HUBUNGAN ANTARA PENERIMAAN DIRI DENGAN QUARTER LIFE CRISIS PADA MAHASISWA - Surya Andika Putri; Zaki Nur Fahmawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Quarter of life crisis is a transitional period for individuals who experience emotional crisis when starting to engage with the real world. Research measures the correlation between self-acceptance and quarter life crisis in college students. The approach used was quantitiative correlational with total sample of 377 students. Data collection uses a self-acceptance scale with a reliability of 0.766 and a quarter life crisis scale with a reliability of 0862. Data analysis used in this study using Pearson's product moment correlation test. This study shows that the results of hypothesis testing obtained with the correlation coefficient r = -0.304 with a significance value of <.001. This shows that there is a significant negative relationship between self-acceptance and quarter life crisis. So, it can be said that when self-acceptance in students is high, the quarter life crisis of students is low, and when self-acceptance in students is low, the quarter life crisis in students is high